A genetic and developmental biological approach for a family with complex congenital heart diseases—evidence of digenic inheritance - Yoshida, Yu; Uchida, Keiko; Kodo, Kazuki; Ishizaki-Asami, Reina; Maeda, Jun; Katsumata, Yoshinori; Yuasa, Shinsuke; Fukuda, Keiichi; Kosaki, Kenjiro; Watanabe, Yusuke; Nakagawa, Osamu; Yamagishi, Hiroyuki (Frontiers in Cardiovascular Medicine, 2023)
Objective: Congenital heart disease (CHD) is caused by cardiovascular developmental defects and has a global prevalence of 1%. The etiology of CHD is multifactorial and remains generally unknown, despite advances in analytical techniques based on next-generation sequencing (NGS). The aim of our study was to elucidate the multi-genetic origin and pathogenesis of an intriguing familial case with complex CHD. Methods: We performed an original trio-based gene panel analysis using NGS of the family, including two siblings with CHD of single ventricular phenotype, and their unaffected parents. The pathogenicity of the detected rare variants was investigated in silico, and the functional effects of the variants were confirmed in vitro using luciferase assays. The combinatorial effect of gene alterations of the putative responsible genes was tested in vivo using genetically engineered mutant mice. Results: NGS-based gene panel analyses revealed two heterozygous rare variants in NODAL and in TBX20 common to the siblings and to just one of parents. Both variants were suspected pathogenic in silico, and decreased transcriptional activities of downstream signaling pathways were observed in vitro. The analyses of Nodal and Tbx20 double mutant mice demonstrated that Nodal+/-Tbx20-/- embryos showed more severe defects than Nodal+/+Tbx20-/- embryos during early heart development. The expression of Pitx2, a known downstream target of Nodal, was downregulated in Tbx20-/- mutants. Conclusions: Two rare variants on NODAL and TBX20 genes detected in this family were considered to be loss-of-function mutations. Our results suggest that NODAL and TBX20 may be complementary for the cardiac development, and a combinatorial loss-of-function of NODAL and TBX20 could be implicated in oligogenic inherence as the etiology of complex CHD associated with single ventricle defects in this family.